Three loop QCD corrections to the heavy-light form factors: fermionic contributions - Sudeepan Datta; Narayan Rana (Journal of High Energy Physics)
Abstract We present analytic results for three-loop fermionic corrections to the heavy-light form factors in perturbative quantum chromodynamics. Specifically, we present all light quark contributions and contributions from two heavy quark loops. We use the method of differential equations to compute all relevant three-loop master integrals. The results for all these contributions are expressed in terms of harmonic polylogarithms and generalized harmonic polylogarithms.